Saliva-Based ELISAs for Effective SARS-CoV-2 Antibody Monitoring in Vaccinated Individuals - Casian, Joseph G.; Angel, Aaron N.; Lopez, Ronell; Bagos, Cedie; MacMullan, Melanie A.; Bui, Mindy L.; Chellamathu, Prithivi; Das, Sudipta; Turner, Fred; Slepnev, Vladimir; Ibrayeva, Albina (Frontiers in Immunology, 2021)
In March 2020, the World Health Organization (WHO) declared a global health emergency—the coronavirus disease 2019 (COVID-19) pandemic. Since then, the development and implementation of vaccines against the virus amidst emerging cases of re-infection has prompted researchers to work towards understanding how immunity develops and is sustained. Serological testing has been instrumental in monitoring the development and persistence of antibodies against SARS-CoV-2 infection, however inconsistencies in detection have been reported by different methods. As serological testing becomes more commonplace, it is important to establish widespread and repeatable processes for monitoring vaccine efficacy. Therefore, we present enzyme linked immunosorbent assays (ELISAs) compatible for antibody detection in saliva as highly accurate, efficacious, and scalable tools for studying the immune response in individuals vaccinated against SARS-CoV-2.